DISEASE DYNAMICS AND CROSS-TRANSMISSION RISKS IN CULTURED AND WILD BARRAMUNDI (Lates calcarifer) IN INNER AMBON BAY, INDONESIA - Borut, Ruku Ratu; Sahetapy, Jacqueline Sahetapy Marleen Francischa; Rijoly, Stefanno Markus Anthony; Tawari, Ruslan Husen Saban; Tuhumury, Julian (Jurnal Riset Akuakultur, 2025)
This study aimed to evaluate the potential infection of bacteria Vibrio spp. and parasites in farmed barramundi (Lates calcarifer) and wild fish inhabiting Inner Ambon Bay. The research was conducted over a five-month period (August–December 2024) using a purposive sampling, to monthly collect and analyse two barramundi populations. Bacteria were isolated from liver and kidney tissues of the collected fish using sea water complate (SWC) agar and tiosulfate citrate bile-salt sucrose (TCBS) agar and identified with the Analytical Profile Index (API) 20 Non-Enteric (NE) kit. Parasitic identification was performed microscopically on gills, skin, and intestinal samples. The results revealed that Vibrio spp. were detected at relatively high abundance, dominated by V. harveyi, V. alginolyticus, and V. vulnificus. Identified parasites included Trichodina sp., Cryptocaryon irritans, Benedenia sp., and nematodes. Parasite infection prevalence in cultured barramundi ranged from 40% to 70%, whereas in wild fish it reached 60%. These findings strongly indicate the potential for cross-transmission of diseases between cultured and wild fish populations in Inner Ambon Bay.Penelitian ini bertujuan mengevaluasi potensi infeksi bakteri Vibrio spp. dan parasit pada ikan kakap putih (Lates calcarifer) budidaya dan ikan liar di perairan Teluk Ambon Dalam. Penelitian dilaksanakan selama lima bulan (Agustus–Desember 2024) dengan metode purposive sampling, masing-masing lima ekor ikan kakap putih budidaya dan lima ekor ikan liar setiap bulan. Isolasi bakteri dilakukan dari organ hati dan ginjal menggunakan media SWC agar dan TCBS agar, sedangkan identifikasi bakteri menggunakan kit API 20 NE. Identifikasi parasit dilakukan melalui pemeriksaan mikroskopis pada organ target, yaitu insang, kulit, dan usus. Hasil penelitian menunjukkan bahwa Vibrio spp. ditemukan dengan kelimpahan relatif tinggi, didominasi oleh V. harveyi, V. alginolyticus, dan V. vulnificus. Jenis Parasit yang teridentifikasi meliputi Trichodina sp., Cryptocaryon irritans, Benedenia sp., dan nematoda. Prevalensi infeksi parasit pada ikan budidaya berkisar 40–70%, sedangkan pada ikan liar mencapai 60%. Hasil penelitian ini mengindikasikan adanya potensi penularan silang penyakit antara ikan budidaya dan ikan liar di Teluk Ambon Dalam.